Comparison of the effects of isoinertial and traditional strength training in male tennis players - Dušan Ćorilić; Boris Karasek; Mladen Mikić (Exercise and Quality of Life)
The goal of the research was to determine the effects of six weeks of isoinertial training on explosive strength, speed, and agility compared to traditional strength training in tennis players. The subjects, thirty male tennis players aged 20 to 35, were divided into three groups: the experimental group 1 (E1; n=10), which performed strength training on an isoinertial device; the experimental group 2 (E2; n=10), which performed traditional strength training; and the control group (C1; n=10). E1 and E2 groups had a total of six weeks of training with two training sessions per week, with three exercises per training session performed in four series for six to eight repetitions. The results showed that isoinertial strength training has a positive effect in the variables squat jump (SJ), countermovement jump (CMJ), 5-meter sprint (5M), 20-meter sprint (20M), agility T-test (T-test), and 505 agility test (505). Post hoc analysis revealed that there are significantly better effects of isoinertial training compared to isodynamic training in the countermovement jump (CMJ), 5-meter sprint (5M), and 20-meter sprint (20M). The E1 group had significantly better results than the C1 group in all tests. The E2 group had significantly better results compared to the C1 group in the variables SJ, 20M, and T-test. The results also show that six weeks of isoinertial training produce better results in the development of variables CMJ and 20M compared to the traditional strength training group. Accordingly, fitness and tennis coaches should also use this training method when working with tennis players.